2013
DOI: 10.3390/min3040427
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Study of a Biologically-Based Treatment System That Removes Arsenic, Zinc and Copper from Landfill Leachate

Abstract: Mineralogical characterization by X-ray diffraction (XRD) and a high throughput automated quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN) was conducted on samples from a sulphate-reducing biochemical reactor (BCR) treating high concentrations of metals (As, Zn, Cu) in smelter waste landfill seepage. The samples were also subjected to energy dispersive X-ray (EDX) analysis of specific particles. The bulk analysis results revealed that the samples consisted mainly of silicate and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…The product sulfide reacts with metal cations to form sparingly soluble metal sulfides [ 67 ]. This has been confirmed as a metal removal mechanism in many constructed wetlands [ 68 ] [ 69 ]. The phylogenetic analysis revealed many OTUs classified as Deltaproteobacteria, which includes most sulfate reducing bacteria.…”
Section: Resultsmentioning
confidence: 76%
“…The product sulfide reacts with metal cations to form sparingly soluble metal sulfides [ 67 ]. This has been confirmed as a metal removal mechanism in many constructed wetlands [ 68 ] [ 69 ]. The phylogenetic analysis revealed many OTUs classified as Deltaproteobacteria, which includes most sulfate reducing bacteria.…”
Section: Resultsmentioning
confidence: 76%
“…There is evidence that sulfate-reducers were more active in the BCR in the past. A mineralogical survey of the same BCR core samples as were used in this study revealed that As and Zn were present mostly as sulfides inside the bioreactor (Khoshnoodi et al, 2013 ). Data collected by the operators from previous years shows that sulfate was being reduced through the system (Mattes et al, 2011 ).…”
Section: Discussionmentioning
confidence: 92%
“…Bioreactors are provided with an organic-rich material, usually a waste product from forestry, pulp and paper, agriculture, or food industries that provides a supply of electron donors to fuel microbial consortia (Lindsay et al, 2008 , 2011 ; Mattes et al, 2011 ; Schmidtova and Baldwin, 2011 ). Microbial activity consumes oxygen to create anaerobic and reducing conditions under which several microbial processes, as well as favorable geochemical conditions, occur that promote metal immobilization: fermentative organisms provide electron donors from decomposing complex organic matter; sulfate- and metal-reducing microbes use these electron donors to produce products that lead to metal immobilization (Jalali and Baldwin, 2000 ; Stolz et al, 2006 ; Khoshnoodi et al, 2013 ); membrane-bound metal transporters assimilate metals into microbial cells where they can be methylated and volatilized, accumulated, or reduced to other redox states (Zhang and Frankenberger, 2000 ; Bentley and Chasteen, 2002 ; Amoozegar et al, 2012 ); extrapolymeric substances and cell walls possess binding moieties for metal ions that act as nucleation sites for biosorption and precipitation (Mullen et al, 1989 ; Jalali and Baldwin, 2000 ; French et al, 2013 ). Despite this myriad of avenues for metal transformation and immobilization, biochemical reactors (BCRs) for treatment of mining-influenced water at industrial sites are often beset with sub-optimal performance or even completely fail to reliably meet water quality objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Organic carbon is utilized in constructed wetland systems and in situ treatment systems and PRBs to promote the growth and activity of sulfate-reducing organisms, leading to the formation of metal sulfide minerals, including sphalerite. The alkalinity generated in these biologically mediated systems also promotes the formation of metal carbonate precipitates that could potentially include hydrozincite. , Zn stable isotope measurements may thus be employed in treatment systems to understand pathways leading to the attenuation of Zn from solution. However, a range of other factors such as the presence of organic matter, secondary mineral precipitates, ionic strength, and speciation of Zn could influence the effectiveness of field measurements. , It is also important to note that although the precipitation results reported here describe equilibrium isotope values, kinetic factors may also play a role in determining Zn isotope fractionation in the environment.…”
Section: Resultsmentioning
confidence: 99%